Cloning and Characterization of ifitm1 and ifitm3 Expression During Early Zebrafish Development - CORRIGENDUM. Issue 1 (21st July 2015) - Xue, Wei-Wei; Wang, Huan-Nan; Wang, Zhi-Meng; Qiu, Meng-Xi; Che, Jing; Deng, Feng-Jiao; Liu, Jiang-Dong
Abstract : The authors apologise for errors in the corresponding authors details given on page 1 of the article. Below is the correct information of the corresponding author and email address : 1) Wei-Wei Xue, Huan-Nan Wang, Zhi-Meng Wang, Meng-Xi Qiu, Jing Che, Feng-Jiao Deng* and Jiang-Dong Liu* 2) *All correspondence to: Feng-Jiao Deng and Jiang-Dong Liu. e-mail:fish4@whu.edu.cn 3) All authors are from the same one laboratory. The second laboratory was superfluous and should be deleted.